2014
DOI: 10.1152/ajpcell.00006.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial inefficiencies and anoxic ATP hydrolysis capacities in diabetic rat heart

Abstract: As ~80% of diabetic patients die from heart failure, an understanding of diabetic cardiomyopathy is crucial. Mitochondria occupy 35-40% of the mammalian cardiomyocyte volume and supply 95% of the heart's ATP, and diabetic heart mitochondria show impaired structure, arrangement, and function. We predict that bioenergetic inefficiencies are present in diabetic heart mitochondria; therefore, we explored mitochondrial proton and electron handling by linking oxygen flux to steady-state ATP synthesis, reactive oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 65 publications
1
56
0
Order By: Relevance
“…The uncoupling of mitochondrial respiration and oxidative phosphorylation, producing the decrease in respiratory control ratio, was evident by 3 months, at which time cirrhosis is evident histologically in the liver. A similar decrease in respiratory control ratio has been observed in failed human myocardial tissue [39], and diabetic hearts were also shown to have lower ATP levels and compromised mitochondrial respiration [40]. An important feature of cellular injury is activation of the mitochondrial permeability transition (MPT) pore, which can be induced by oxidative stress [41].…”
Section: Liver Cirrhosis Induces Significant Functional Alterations Imentioning
confidence: 61%
“…The uncoupling of mitochondrial respiration and oxidative phosphorylation, producing the decrease in respiratory control ratio, was evident by 3 months, at which time cirrhosis is evident histologically in the liver. A similar decrease in respiratory control ratio has been observed in failed human myocardial tissue [39], and diabetic hearts were also shown to have lower ATP levels and compromised mitochondrial respiration [40]. An important feature of cellular injury is activation of the mitochondrial permeability transition (MPT) pore, which can be induced by oxidative stress [41].…”
Section: Liver Cirrhosis Induces Significant Functional Alterations Imentioning
confidence: 61%
“…ATP production was measured simultaneously with respiration rates using Magnesium Green™ (MgG, ThermoFisher Scientific, Waltham, MA, USA) fluorescence (ex/em, 503 nm/530 nm), based on previous work 3234 . Flight muscle was prepared as previously described before being added to the chamber.…”
Section: Methodsmentioning
confidence: 99%
“…PM and G3P-supported respiration protocols were conducted as described above. ATP production signal was calibrated based on previous work by conducting a separate titration of ATP and ADP up to 5 mM 32 . ATP production rates were then determined by expressing this change in ATP concentration over time in Excel (Microsoft, Redmond, WA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In chronic Type 1 diabetes (OVE26 mice) mice model, it was demonstrated that mice had evidence of mitochondrial biogenesis that was coupled to a reduction in mitochondrial function and mitochondrial ultrastructural defects [57]. Mitochondrial state III respiration is significantly reduced in type 2 diabetic animal models (db/db and ob/ob) [5860]. Furthermore, there is evidence for increased cardiac mitochondrial biogenesis with ultrastructural defects in insulin resistance and diabetes animals [59, 6164].…”
Section: Mitochondrial Dysfunction In Diabetic Heartmentioning
confidence: 99%